Políticas públicas para indígenas em Belém: como avaliam os beneficiários - FERNANDES, Kassya Cylene Assunção (Universidade Federal do Pará, 2024)
Since the Federal Constitution of Brazil of 1988, and with a series of other legal milestones, notably the International Labor Organization's Convention 169, methodologies have been discussed and developed to amplify the voices of those who would benefit from public policies. However, experiences in this regard in Belém, the capital of the State of Pará and one of the municipalities with the most political importance in the Amazon, are still incipient. The research proposed to update studies on public policies for urban indigenous people in Belém and to listen to the beneficiaries on how they evaluate the quality and how they consider public policies should be. As main results, the indigenous people evaluate that public policies still need greater focus on the specificities of this public, as they do not address the complexities experienced by descendants of native peoples in the city.